Mapping the research landscape of artificial hearts: identifying hotspots and frontiers through bibliometric analysis - Peng, Yufeng; Peng, Kewei; Li, Luyao; Xiong, Fanglei (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe rising prevalence of advanced heart failure and the shortage of donor hearts underscore the need for artificial hearts. Technological evolution from pneumatic to magnetically levitated systems has occurred, yet critical challenges persist in hemocompatibility, anticoagulation, and transcutaneous energy transmission systems.MethodsWe conducted a bibliometric analysis of 6,310 publications from the Web of Science Core Collection using CiteSpace, VOSviewer, and Bibliometrix. This study aimed to delineate research trends, collaboration patterns, and technological advancements in the artificial heart field.ResultsGlobal publications showed a 13.9% average annual growth, with citations surging 260-fold. The USA leads research output, with China demonstrating rapid growth. Research focus has shifted from ventricular assist devices towards artificial intelligence control strategies. Magnetic levitation continuous-flow total artificial hearts and soft TAHs emerge as key technological innovations. Frontier research includes biohybrid systems and transcutaneous wireless power transfer.ConclusionArtificial heart research displays a three-stage progression: clinical need-driven, technology integration, and intelligent innovation. Enhanced interdisciplinary collaboration is vital to address persistent challenges in biocompatibility optimization and personalized anticoagulation. This is crucial for transitioning the treatment paradigm from mechanical replacement towards physiologically adaptive, long-term solutions.